Suspicion of madness - Parker, Barbara (Barbara J.) (New York : Signet, 2003)
Gail and Anthony find their quiet getaway in the Florida Keys interrupted when a former client is implicated in a local murder and subsequently attempts suicide during a tropical storm.
National College of Business and Arts
Keywords: Women lawyers -- Fiction; Detective and mystery fiction